1997
DOI: 10.1001/jama.1997.03540440052032
|View full text |Cite
|
Sign up to set email alerts
|

Depressive Symptoms and the Cost of Health Services in HMO Patients Aged 65 Years and Older

Abstract: Depressive symptoms in older adults are associated with a significant increase in the cost of medical services, even after adjusting for the severity of chronic medical illness.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

8
136
0

Year Published

1998
1998
2012
2012

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 547 publications
(144 citation statements)
references
References 61 publications
8
136
0
Order By: Relevance
“…Contrary to our findings within the sample of healthy individuals, a greater proportion of younger patients with long-term medical conditions presented GHQ scores indicative of severe psychological distress. Although studies in the general population that included medical comorbidity as a covariate reported that young people experience a higher prevalence of psychological distress than older groups irrespective of the presence of chronic conditions [21], studies in the primary care setting provided evidence that younger patients may be more vulnerable to psychological distress, in line with the present findings [50][51][52]. Our findings are further supported by a study from eight US primary care sites [20].…”
Section: Discussionsupporting
confidence: 89%
“…Contrary to our findings within the sample of healthy individuals, a greater proportion of younger patients with long-term medical conditions presented GHQ scores indicative of severe psychological distress. Although studies in the general population that included medical comorbidity as a covariate reported that young people experience a higher prevalence of psychological distress than older groups irrespective of the presence of chronic conditions [21], studies in the primary care setting provided evidence that younger patients may be more vulnerable to psychological distress, in line with the present findings [50][51][52]. Our findings are further supported by a study from eight US primary care sites [20].…”
Section: Discussionsupporting
confidence: 89%
“…[28][29][30][31] As a result, depression remains a difficult condition to treat. 32 Thus, preventing depression may be more sensible, and perhaps more cost-effective, than waiting to treat it once it occurs or failing to treat it at all.…”
Section: Commentmentioning
confidence: 99%
“…Depression burdens nearly one in six persons over age 65 with substantial morbidity, mortality, and costs (1)(2)(3). Although treatment consists almost entirely of antidepressants (4,5), pharmacotherapy for depression among older populations can be problematic (6,7).…”
mentioning
confidence: 99%